Protective effects of Alternanthera sessilis ethanolic extract against TNF-α or H2O2-induced endothelial activation in human aortic endothelial cells - Mohd Razali, Nur Nadia; Soek, Sin Teh; Siau, Hui Mah; Yoke, Keong Yong; Chin, Theng Ng; Yang, Mooi Lim; Lai, Yen Fong (Hindawi Publishing, 2022)
Activation of the endothelium has been shown to contribute to the early stage of vascular diseases such as atherosclerosis and hypertension. In endothelial activation, excess reactive oxygen species (ROS) production and increased expression of cell adhesion molecules cause an increase in vascular permeability. Alternanthera sessilis (L.) R. Br. is an edible traditional herbal plant, which has previously been shown to possess antioxidant and anti-inflammatory effects. However, the effect of A. sessilis on the activation of human aortic endothelial cells (HAECs) remains unknown. This study aimed to investigate the effects of A. sessilis on endothelial permeability, vascular cell adhesion-1 (VCAM-1) expression, production of ROS and hydrogen peroxide (H2O2), and superoxide dismutase (SOD) and catalase (CAT) activities. The viability of HAECs was first determined using the MTT viability assay. The effect of A. sessilis on endothelial permeability was examined using the FITC-dextran permeability assay. Besides, enzyme-linked immunosorbent assay (ELISA) was done to assess soluble VCAM-1 (sVCAM-1) expression. The production of ROS and H2O2 was studied using 2′,7′-dichlorodihydrofluorescein diacetate (H2-DCFDA) and Amplex Red fluorescent dyes, respectively. SOD and CAT activities were also measured using commercial kits. Our results showed that 25–200 μg/mL of A. sessilis ethanolic extract did not cause significant death in HAECs. A. sessilis at 200 μg/mL significantly inhibited TNF-α-induced hyperpermeability of HAECs. However, A. sessilis did not reduce increased VCAM-1 expression induced by TNF-α. A. sessilis also significantly reduced TNF-α-induced increased ROS production, but not H2O2 production. Furthermore, 100 μM of H2O2 decreased both SOD and CAT activities in HAECs at 2 h. A. sessilis ethanolic extract dramatically increased both reduced SOD and CAT activities caused by H2O2. The liquid chromatography-mass spectrometry (LC-MS) analysis of A. sessilis ethanolic extract demonstrated the presence of arachidonic acid, azadirachtin, astaxanthin, flavanole base + 3O, 2Prenyl, and vicenin 2, while the gas chromatography-mass spectrometry (GC-MS) analysis showed that the extract contains 1,3,5-dihydroxy-6-methyl-2,3-dihydro-4H-pyran-4-one, 3-deoxy-d-mannoic lactone, 4-pyrrolidinobenzaldehyde, and n-hexadecanoic acid. In conclusion, our findings suggest that A. sessilis ethanolic extract protects against endothelial hyperpermeability and oxidative stress elicited by pro-inflammatory or prooxidant stimulus. This study reveals a therapeutic potential of A. sessilis in preventing endothelial activation, which is a key event in early atherosclerosis.